IMPLEMENTASI PENGIRIMAN MAIL DAN LOGISTIK PADA PT. POS INDONESIA (PERSERO) CABANG BANJARMASIN - Dwi Retnosari (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2017)
This study aims to develop a system of mail and logistics delivery management application at PT. Pos Indonesia (Persero) Banjarmasin branch, This system is designed to facilitate the implementation of delivery services, mail collection and logistics package. The system to be created can handle data collection of mail and parcel deliveries, both incoming and outgoing mails, and return shipping returns.  The process of making this system is done by Data collection ie Finding the available data that facilitate the process of problem solving and then determine the information system that must be done by studying the system and the work process of the previous system to build a new system, after that done the system testing process, Making this System Using computerized system that is online using web with programming language of php, javascript and css. The development of this system will further facilitate the management of data in the process of data collection, mail delivery and logistics.  The results of this study indicate that by developing the previous system, the delivery of mail or package can be monitored the process and handling any problems that occur in the delivery process can be addressed, This system can also facilitate the process of sending mail or packages and shorten the working time. Keywords: Mail & Logistic, Web